Study case ratio gear of stepper motor on electronic throttle using PID control - Ayu Sandra Dewi; Zainal Arifin; I Wayan Adiyasa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
The throttle is a component that determines the amount of airflow into the combustion chamber. The latest in-vehicle technology makes it possible to adjust the fly valve electronically. The electronic system adjusts the angle size by comparing the predetermined setpoints. In research, electronic system designs are based on existing models. The throttle model uses a stepper motor drive. Electronic control using a microcontroller with proportional-integral-derivative (PID) control. While the setpoint is based on a reference from the throttle position sensor (TPS) sensor. The greater the throttle reference value, the greater the angle opening of the butterfly valve. The results of this study obtained a simulation model of electronic throttle control from gear ratios of 1: 1, 5: 1, and 10: 1 for conventional vehicles.